IMPLEMENTATION OF HELPDESK CHATBOT APPLICATION FOR INFORMATION SYSTEM SERVICES IN HIGHER EDUCATION - Sumiyati; Rahayu, Puji; Adiwinata, Calvin; Marbun, Rosmalinda (Department of Informatics Engineering, Faculty of Science and Technology, Universitas Islam Negeri Alauddin, Makassar, Indonesia, 2024)
This study implements a helpdesk chatbot application for information system services in higher education. The background is the students' need for quick and accurate academic information, especially during the Covid-19 pandemic. The method used is the waterfall model, with data collection stages through questionnaires, observation, and literature study. The development result is a web-based chatbot application that can automatically answer student questions related to academic information systems. Testing shows that this application successfully improves information service efficiency, reduces the workload of helpdesk admins, and increases user satisfaction. In conclusion, this helpdesk chatbot is effective in providing information to students anytime and anywhere, with recommendations for further development in the future.